Research Phenomenon during the Covid-19 Pandemic: Challenges and Opportunities for Online Media Learning - Harry Satrya Wanto; Suharnanik Suharnanik; Soepriyono Soepriyono (Budapest International Research and Critics University, 2021)
Covid research during a pandemic is research carried out to involve oneself so that research continues to run optimally, even though it is limited by space and social mobility. The learning system has undergone a change where previously using offline or face-to-face then becoming online media. This effort is carried out so that the impact can be suppressed and to break the chain of transmission of the pandemic. This research was carried out using health protocols, the method used was more of a survey nature, monitoring the evaluation of online learning media during the pandemic. By using online media to reach research respondents. This research is sporadic regardless of the area where the respondent is located. This study uses online media, conducts online media learning surveys and optimizes data findings obtained during later research. This study was analyzed based on facts that occurred in several places affected by the pandemic, for example how lecturers and students applied online media as an effort to implement health protocols. The results of this study based on data distributed through the online learning process and reference studies show that media learning can be a challenge and opportunity in terms of changing behavior during online learning, quality of education, learning facilities and online learning methods.